Morphological variation of the Bicornucythere bisanensis complex (Ostracoda, Crustacea), with a description of a new species - Wang, Yunan; Wang, Yaqiong; Fan, Daidu; Miao, Kejia; Zhou, Baochun (Zootaxa, 2026)
The Bicornucythere bisanensis complex is a species group of trachyleberidid Ostracoda found in shallow-sea sediments along the margin of the East China Sea, which contains three members, namely Bicornucythere bisanensis, B. misumiensis, and Form G. In this study, we analyzed the ontogenetic changes in carapace morphology of B. bisanensis and Form G from the East China Sea and compared them with the specimens of the B. bisanensis complex from the South Yellow Sea, the Leizhou Peninsula, and those in the published literatures, in order to reveal the similarities and differences between the three members. Our results indicate that Form G resembles the young instars of B. bisanensis in carapace size, shape and the fossae arrangement pattern (FAP) on the carapace surface. Our results also show significant differences between Form G and the other two members; B. bisanensis and B. misumiensis share a relatively large carapace size (L=0.66–0.95 mm), a sub-rectangular lateral outline and the same FAP, whilst Form G has a small, sub-triangular carapace (L=0.51–0.66 mm) and a FAP with nine fewer fossae. We concluded that the sub-triangular carapace outline and the peculiar FAP in Form G are species-specific, and we described Form G as a new species, Bicornucythere zhaoi sp. nov. A few individuals with small, sub-triangular valves and an intermediate type of FAP between B. bisanensis and B. zhaoi sp. nov., which were tentatively named Bicornucythere aff. zhaoi, were discovered from the Pliocene Leizhou Peninsula where it co-occurred with B. bisanensis. Their occurrence may suggest that the latecomer B. zhaoi sp. nov., which does not appear until late Pleistocene, is descended from B. bisanensis by paedomorphosis.